Sanctions in the it sphere during the USSR, analysis of the reasons for dependence on western technologies - V. V. Manuylenko; S. V. Tishchenko (Вестник Северо-Кавказского федерального университета)
Introduction. Already by the beginning of the 2000s, specialists understood a significant technological lag of the Russian industry in the IT industry. After the sanctions pressure on Russia intensified in 2014, and then in 2022, the consequences of sanctions in this area were assessed as critical with high risks for the economy in terms of the degree of negative impact. The sources of this lag should be considered in retrospect of the sanctions imposed in high-tech industries by Western countries on the Soviet Union since the 40-50-ies of the last century. In addition, it is necessary to analyze the mistakes in the construction of long-term plans for the development of the IT economy, which were made by the USSR government. Goal. The study considers the retrospective of sanctions in the IT industry, analyzes the reason for the technological lag. Materials and methods. The study is based on a comparative analysis of the sanctions imposed against the USSR and a critical analysis of the measures taken by the Government of the Union in the field of computer technology development. Results and discussion. In the course of the work, the formation of prerequisites for lagging behind in the areas of high-tech computer production and software creation, due to Western sanctions and mistakes made in the country's economic policy, is shown. Conclusion. The sovereignty of Russia in the field of modern microelectronics and software can be restored, since for this purpose the country has a scientific school, its own technological developments and the raw material base that can meet all the needs of the industry.